STATISTICAL CHARACTERISTICS OF OCULAR BLOOD FLOW UNDER CAROTID ARTERY STENOSIS REFLECT VESSEL IMPAIRMENT AS STROKE BIOMARKER - ISMAIL, AISHAH (2020)
Atherosclerosis, the major underlying cause of stroke, asymptomatically reduces blood flow to the brain and the eye, resulting in ocular impairment. However, real-time investigation of ocular blood flow (OBF) impairment under common carotid artery (CCA) stenosis is vague. This thesis aims to assess the impact of CCA stenosis on OBF longitudinally using a rabbit model. The OBF impairment was characterized to provide information about the impaired vessel condition. With these, the OBF characteristics were further classified to identify the potential biomarkers indicating impaired vessel conditions, hence providing information that indicates the risk of stroke onset. About 75% stenosis was created by tying the CCA with a plastic mandrel using a 9-0 nylon suture.